Probing the atom : interactions of coupled states, fast beams, and loose electrons - Silverman, Mark P. (Princeton University Press, 2000)
"This book gives an in-depth account of the author's own penetrating experimental and theoretical investigations of the hydrogen atom, while simultaneously providing broad lessons in the application of quantum mechanics to atomic structure and interactions."--Jacket